Legal Vacancy in Law Number 5 of 1960 concerning Basic Agrarian Regulations and its Implications for the Protection and Legal Certainty of Land Rights in Indonesia - Boy Nurdin; Wahyu Widodo; Daud Juristo Chiang (International Journal of Law and Society, 2025)
Land issues in Indonesia show complex dynamics due to legal vacuum and legal loopholes in the applicable land law system. This condition is exacerbated by the weakness of implementing regulations of the UUPA which are unable to respond to developments in the era, thus opening up space for land mafia practices and overlapping development policies. This legal vacuum impacts violations of community rights to land, environmental degradation, and the failure to realize optimal legal protection. The study uses a normative legal approach based on secondary data from literature studies to analyze the urgent need for land law reform. The findings reveal the need for the land law system renewal to create stronger protection of community rights and ensure a sustainable development direction by environmental conditions.